Students’ Social Skills to Improve Social Inclusion in Schools - Rosita, Tita; Rahma, Dita Padiani; Wijaya3, Raden Mutiara Puspa; Widiastuti, Ratih (Proceedings of Siliwangi Annual International Conference on Guidance and Counselling, 2024)
Indonesia has a high commitment in organizing inclusive education, but there are several problems in inclusive schools, namely children with special needs often feel isolated in their classes, get bullied by their peers, and they are not socially integrated. The purpose of this study is to analyze aspects of students' social skills to improve social inclusion in schools, so that children with special needs get good acceptance by their peers and academically have meaningful learning. Based on the results of the literature study review, the aspects of social skills that students need to have in improving social inclusion are (1) students' social interaction skills with their friends who have special needs, (2) students' social awareness of their differences with their friends who have special needs, (3) students' emotional control in dealing with their friends who have special needs, and (4) students' participation skills to be able to involve their friends who have special needs in the peer group social structure. It is hoped that by developing these aspects of social skills, it can improve social inclusion in schools, so that students with special needs can be integrated both socially and academically.